Penggunaan Media YouTube Ustadz Hanan Attaki dalam Aktivitas Dakwah - Efendi, Erwan; Ardianti, Hafizda; Dwi, Rahma (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
With the advancements in today's era, it is possible to create da'wah activities through social media, one of which is YouTube media. YouTube media is used by preachers to convey their preaching with the values conveyed in a simple and interesting way. The reason a preacher uses YouTube media for preaching activities is because YouTube media makes it easier and expands the preaching network that has been conveyed by the preachers. And the results in this research discuss the use of Ustadz Hanan Attaki's YouTube media in da'wah activities. It is true that the author knows that Ustadz Hanan Attaki uses all social media such as Instagram, Tiktok and YouTube. However, Ustadz Hanan Attaki in conveying his da'wah was more active in using YouTube media. One of the reasons why Ustadz Hanan Attaki made this YouTube media is because according to him, with this media it is easier to achieve the intended target and be accepted by someone, one of which is teenagers. And Ustadz Hanan Attaki in his preaching really maximizes YouTube media, his preaching content is designed and packaged as well and as attractively as possible so that it is in great demand among the public. The aim of this research is to find out how YouTube media is used in da'wah activities carried out by Ustadz Hanan Attaki. This research uses a quantitative approach, the data analysis carried out by the researcher is descriptive analysis, which uses regression tests, multiple linear tests, correlation coefficient tests and determination. Because the results of this research show a very high level on Ustadz Hanan Attaki's YouTube channel which currently has 2.58 million followers, 203 thousand views, and has 276 videos on it, this can have a positive influence on Hanan Attaki's YouTube channel. The YouTube media he uses to convey his preaching, which means that the more preaching material he conveys, the higher the level of positivity for listeners and viewers.